Design of a Prototype Web-based System for Monitoring New Customer Installation Administration using a User-Centered Design Approach - Rahmat Hidayat; Ahmad Fauzi (Universitas Islam Indragiri, 2026)
Monitoring the administrative status of new customers in electricity service environments is still largely dependent on conventional methods, resulting in delays in information delivery, data recording errors, and limitations in comprehensive data oversight. This study aims to develop a prototype web-based system for monitoring the administrative status of new customer installations at PT PLN (Persero) ULP Subang by applying a user-centered design approach. The research adopts the User-Centered Design (UCD) methodology, which consists of four main stages: context-of-use analysis, user requirements identification, design solution development, and evaluation of the proposed design. The prototype was developed using Figma and includes features such as a monitoring dashboard, customer data input, data search, and administrative status updates. The system was evaluated using the System Usability Scale (SUS). The findings indicate that the system achieved an average SUS score of 75.5, which falls into the “good” category, suggesting that the system has an acceptable level of usability and is capable of supporting administrative monitoring activities more effectively.